Moderate-intensity Exercise Decreases Cortisol Response in Overweight Adolescent Women - Yasep Setiakarnawijaya; Widiastuti Widiastuti; Muhamad Syamsul Taufik; Kuswahyudi Kuswahyudi; Awaluddin Awaluddin; Ibnu Sina; Andi Hasriadi Hasyim; Hasyim Hasyim; Abdul Hafidz; Nur Ahmad Muharram (OVS LLC, 2022)
The study purpose was to demonstrate the effect of moderate-intensity exercise on reducing cortisol levels in overweight adolescent women. Materials and methods. This study is an actual trial study with a pre-test randomized control group design involving 20 overweight adolescent women aged 19-22 as research subjects who were randomly divided into two groups, namely CNG (n = 10, control group) and EXG (n = 10, moderate-intensity exercise group). The moderate-intensity exercise intervention was performed for 40 minutes on a treadmill. Cortisol levels were measured using an Enzyme-linked immunosorbent assay (ELISA) kit. Data analysis technique used t-test of independent samples and correlation test using Pearson's correlation coefficient with Statistical Package for Social Sciences (SPSS) version 21. Results. Cortisol levels were obtained as a result of the best means between CNG and EXG (222.57 ± 56.04 vs 225.56 ± 63.96 ng/mL, (p ≥ 0.05)), post-test cortisol levels between CNG and EXG (238, 27 ± 77.94 vs 118.13 ± 12.90 ng/mL, (p ≤ 0.001)) and cortisol Δ between CNG vs EXG (15.71 ± 13.14 vs -107.43 ± 21, 13 ng/mL, (p ≤ 0.001)). Cortisol levels also showed a positive relationship with markers of overweight (p ≤ 0.05). Conclusions. Based on the study results, it was concluded that the cortisol response decreased after moderate-intensity exercise and found a positive relationship between cortisol levels and markers of overweight. These results could be used as a long-term approach to modifying an active lifestyle to reduce stress levels.